Fairgoer in Court of the Universe - R.B.:::::::::
Note with EXP915a_1067a - EXP915a_1073a: Columbus Day Sunday, Oct. 12 - was observed Sat. Oct. 11,1914 - with a water pageant along the Marina - Italian pop & K of C participated - It was a brilliant event and a great attraction even in the unfinished condition of the grads. & buildings, 23,748 paid to enter. Written on photo: 10/11/14.